Developing a Systematic Framework to Assess Climate Change Impacts on Qatar’s Power Systems: A Transition of Adaptation and Mitigation - Aysha F. Jiffry; Dhabia M. Al-Mohannadi (Chemical Engineering Transactions)
The rise in global warming has caused severe climate change impacts in the Arabian Peninsula resulting in an increased electricity consumption and increased CO2 emissions. Several regions have become more vulnerable to impacts such as sea level rise, extreme weather conditions and floods. This work develops a systematic framework to assess the impacts of climate change on the power sector in the state of Qatar. Most of its industrial infrastructure is located in the coastal region. Therefore, a systematic four-step approach is designed to analyse when and how climate change driven hazards affect power facilities in Qatar. The first step of this approach predicts the impacts and risks of climate change which is followed by the measurement of the impact and risks. The third step evaluates mitigation and adaptation strategies and lastly an analysis that facilitates the allocation of investments for the set strategies. The systematic framework is demonstrated using a case study, Ras Abu Fontas Power plant in Qatar. Based on the estimated risk and cost benefit analysis, the power plant is exposed to risks such as floods, coastal erosion and power outage. From the cost benefit analysis out of the three strategies suggested, investment in a sea wall is expected to give the highest net benefit of 4-6 million USD at both emissions scenarios when invested in period 1. Relocation of the plant and investing in a new power solar plant expected to give losses at 450-550 million USD and 400-500 million USD respectively at both scenarios. Investing in a sea wall allows 90 % of the investment to be recovered in 5 years when invested in period 1, whereas the other measures go at a loss regardless of the investment period.